Produção de mutantes de Streptomyces clavuligerus nos genes lat, cvm7P e rpoZ e estudo de seus efeitos sobre a produção de ácido clavulânico - Lima, Vanderlei Aparecido de (Universidade Federal de São Carlos, 2010)
Molecular biology and genetic engineering have been deployed widely in recent years, several protocols have been established, presenting new methodologies capable of altering the genetics of bacterial strains industrial interest. This research had as main objectives: (1) the construction of the following plasmids: plat, pAMB4 and pAMB3RpoZneo, (2) the production of Streptomyces clavuligerus mutants by gene disruption, by insertion of plasmid integrative, and by replication of multi-copy plasmid in Streptomyces clavuligerus by conjugation and (3) study the effect of these mutations on clavulanic acid production and lipolytic activity. In Spain (University of Leon), six mutants Streptomyces clauligerus lat::apr, Streptomyces clavuligerus cvm7P::neo, Streptomyces clauligerus Lat::apr cvm7P::neo, Streptomyces clavuligerus pRAneoZ, Streptomyces clavuligerus pAMB4 and Streptomyces clavuligerus pAMB3RpoZneo were produced. In Leon, the fermentations were performed with the SA culture medium and only with the mutants Streptomyces clavuligerus lat::apr and Streptomyces clavuligerus pRAneoZ. In this case, there was no statistically significant difference at 5% probability by analysis of variance (ANOVA). In Brazil, the fermentations with all mutants in the culture medium-based oil and soybean meal, showed a different pattern in the production of clavulanic acid. The mutants Streptomyces clavuligerus pAMB3RpoZneo and Streptomyces clavuligerus pRAneoZ (= 5%) showed clavulanic acid titles higher when compared with the wild type. The double mutant Streptomyces clavuligerus lat::apr cvm7P::neo, contrary to expectations, showed the lowest levels of clavulanic acid in relation to its parental strain. Streptomyces clavuligerus pRAneoZ mutant and the mutant Streptomyces clavuligerus pAMB4 control, showed the highest lipolytic activity at 5% probability. The double mutant in turn, had the lowest lipolytic activities. A direct relationship between levels of clavulanic acid and lipase production was observed. All mutants produced in this work could be fermented into bioreactor to assess production levels of clavulanic acid and lipase. The construction of a new double mutant named Streptomyces clavuligerus lat::apr RpoZneo from existing ones mutant could be of great interest to investigate this new combination of mutations on clavulanic acid production and lipolytic activity.
Production of Streptomyces clavuligerus mutants in the genes lat, cvm7P and rpoZ, and study their effects on acid production clavulanic
Keywords: Engenharia genética; Plasmídeos; Conjugação bacteriana; Conjugantes; Escherichia coli; Fermentação; Integrativo; Replicativo; Escherichia coli ET12567[PUZ8002]; Conjugantes; Lipase; Atividade lipolítica; Biotecnologia de microrganismos; Plasmids; Integrative; Replicative; Escherichia coli ET12567[PUZ8002]; Conjugation; Exconjugants; Fermentation; Lipase; Lipolytic activity; Microbial biotechnology; ENGENHARIAS::ENGENHARIA QUIMICA